The Effect of Lecture, Brainstorming, Demonstration Towards Breast Self-Examination Behavior Based on Health Belief Model - Emmy Mulyani; Mira Triharini; Tiyas Kusumaningrum (Pediomaternal Nursing Journal, 2021)
Introduction: Breast cancer is the leading cause of cancer-related disability and death in women due to a lack of education using Lecture, Brainstorming, Demonstration (LBD) on Breast Self-Examination (BSE) behaviour in adolescents.Methods: This research was a quasi-experimental research with pre-post treatment and control groups. Fifty-six respondents were selected by purposive sampling. Data were obtained using a questionnaire then analyzed using the Wilcoxon Signed Rank Test and the Mann Whitney U test with a significance level p < 0.05.Results: LBD significantly improved BSE behaviour in young women by perceived susceptibility, perceived severity, perceived barrier, perceived benefit, and perceived self-efficacy (p = 0.00).Conclusion: Delivering LBD health education methods can boost perceived susceptibility, perceived severity, perceived barrier, perceived benefit, perceived self-efficacy of teenagers regarding SADARI behaviour. Teenagers are given health education to increase their knowledge of breast cancer.